A collaboration model for product development through the integration of PLM and SCM in the cabling industry. (2nd February 2022) - Benabdellah, Ghita Chaouni; Bennis, Karim
Managing the product development is a challenging mission. The leading companies adopt product life cycle management (PLM) to manage information while considering collaboration between different product lifecycle phases. Despite the theoretical and scientific background used in PLM researches, the models are still not generalisable for different domains and do not combine PLM systems with supply chain and firm performance, besides, industrial applications are missing. In this regard, the main objective of this paper is to first address a systematic review from 2000 to 2020 by investigating the past and current research of PLM models, supply chain actors and performance. The key problems and issues are also discussed. Second, we propose a collaborative model for the management of the product information the integration of the PLM system, the actors of the supply chain and the performance criteria. Furthermore, to validate the proposed model, we implement a PLM system for an international cabling company.